Productivity, hours worked, and tax/benefit systems in Europe and beyond - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2006)
We analyse the development of labour productivity and hours worked by the working-aged population in the EU25 countries and other OECD countries in 1960-2004. We emphasise the possible effects of taxes, benefits and other labour-market variables. First, we describe the trends in productivity and hours worked especially in the EU15 countries relative to the United States. Then we use both cross-section analyses of the 1995-2004 period and pooled least squares panel data analyses of the 1960-2004 period to explain the developments. Taxes and gross replacement rates do not correlate with productivity growth. Instead, productivity growth is influenced positively by investment into fixed assets, R&D and ICT, higher levels of education, and lower product market regulation. According to the results, taxes and gross replacement rates do have a negative effect on the average number of hours worked. Also the ratio between collective bargaining coverage and trade union density as well as higher product market regulation seem to have a negative effect on the number of hours worked.
Keywords: O47; J24; O57; C33; 330; Productivity; growth; hours worked; convergence; Sozialprodukt; Wirtschaftswachstum; Arbeitszeit; Steuersystem; Soziale Sicherung; EU-Staaten; OECD-Staaten